Fatih Akin's cinema and the new sound of Europe - Gueneli, Berna (Bloomington, Indiana : Indiana University Press, 2019)
At a time when belonging and identity in Europe is complicated by questions of race, ethnicity, religion, and citizenship, Berna Gueneli explores the transnational works of acclaimed Turkish-German filmmaker and auteur Fatih Akın, demonstrates how Akın's aesthetics intersect with politics to reshape notions of Europe, European cinema, and cinematic history.
Cover; Title; Copyright; Dedication; Contents; Acknowledgments; Introduction: Fatih Akın: A Contemporary Filmmaker from Germany; Chapter 1. Mapping Europe: The Road Movie Genre and Transnational European Space in Film; Chapter 2. The Sound of Polyphony: Multilingualism, Multiethnicity, and Linguistic Empowerment in Head-On; Chapter 3. The Sound of Music: Transnational Soundscapes; Chapter 4. Expanding the Scope of European Cinema: Akın's Cinematic Imagining of a Diverse Europe in Context; Conclusion: Intertextual Film-Transnational Film-Transnational Film History
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed February 1, 2019).
JSTOR
Keywords: Akin, Fatih, -- 1973- -- Criticism and interpretation; Akin, Fatih, -- 1973- -- Criticism and interpretation; Akin, Fatih, -- 1973-; Akin, Fatih -- 1973-; Bibel; Motion picture producers and directors -- Germany -- Bibliography; Motion pictures -- Germany -- History -- 21st century; Motion pictures -- Europe -- History -- 21st century; Cinéma -- Allemagne -- Histoire -- 21e siècle.; Cinéma -- Europe -- Histoire -- 21e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Entertainment & Performing Arts; PERFORMING ARTS -- Reference; Motion picture producers and directors; Motion pictures; Europe; Germany; 2000-2099; Bibliographies; Criticism, interpretation, etc; History